2018
DOI: 10.1101/466003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First Report of Recurrent Genomic Selection with Real Data in Popcorn and Genetic Gain Increases

Abstract: Recurrent Selection increases the frequencies of favorable alleles for economically important traits, which in the case of popcorn are popping expansion and grain yield. However, is time-consuming, since each selection cycle consists of three stages: progeny development and evaluation, and recombination of the best families. With the Recurrent Genomic Selection use, the time required for each selection cycle can be shortened, as it allows the evaluation and recombination phases to be performed simultaneously, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…RGS was first reported in popcorn to enhance genetic gain in a breeding population. It has been observed that the recurrent genomic showed higher genetic gain provided that the selection intensity along with genotyping helps in increasing the number of individuals for selection (Schwantes et al 2018). In regarding to RGS, more studies are required, to determine that the genomic prediction model can be applied for how many recurrent selection cycles to predict the genomic estimated breeding value (GEBV) precisely.…”
Section: Recurrent Genomic Selection: An Emerging Approachmentioning
confidence: 99%
“…RGS was first reported in popcorn to enhance genetic gain in a breeding population. It has been observed that the recurrent genomic showed higher genetic gain provided that the selection intensity along with genotyping helps in increasing the number of individuals for selection (Schwantes et al 2018). In regarding to RGS, more studies are required, to determine that the genomic prediction model can be applied for how many recurrent selection cycles to predict the genomic estimated breeding value (GEBV) precisely.…”
Section: Recurrent Genomic Selection: An Emerging Approachmentioning
confidence: 99%
“…However, as usually the evaluation step requires the synthesis and evaluation of progenies of each individual on a experimental trial, this leads to a low genetic gain per unit of time, as it might take too much time to accomplish a cycle. But, with genomic selection it is possible to combine evaluation and recombination into a single step, where the genomic estimated breeding value is used to select the individuals and cross them, without the need to evaluate their progenies (Schwantes et al, 2018).…”
Section: Prefacementioning
confidence: 99%